PRIMER REGISTRO DE ANIDACIÓN DE LA OROPÉNDOLA DE MOCTEZUMA (PSAROCOLIUS MONTEZUMA) EN PLANTAS DE COCOTERO (COCOS NUCIFERA) - Sánchez Soto, Saúl; Gómez Martínez, Ulda Nury (Instituto de Ecología, A.C., 2013)
On March 23, 2012 four colonies of Psarocolius montezuma nesting in coconut plants (Cocos nucifera) were observed on the coast of the municipality of Cardenas, Tabasco, Mexico. A total of 14 plants with nests were quantified, having an overall average of 23.5 nests per colony and 6.7 nests per plant. It is the first nesting record of P. montezuma in coconut plants in the Neotropic.